Leaders, Managers and Leadership, in Educational Institutions - Siti Ulyani, Aap; Machdum Bachtiar; Anis Fauzi (Kirana Publisher (KNPub), 2024)
There are three factors that influence the quality of education not to increase evenly. First, national education policies and implementation are not implemented consistently. Second, the administration of education has long used a centralized system. Third, the participation of the community, especially parents, in implementing education is very minimal. The third factor above focuses on leadership factors, behind the success of an educational institution, there is an important role of individuals who hold leadership roles. Qualitative research was used in this research. The method used in this research is the library research method which is carried out by collecting data from books, journals and articles. Leaders in educational institutions have a very important role in creating an environment conducive to learning. They must be able to plan educational strategies, manage resources, inspire teachers and students, and establish relationships with all educational stakeholders. Leadership functions in educational institutions include planning, organizing, implementing, monitoring and evaluating.